Pengaruh Sikap dan Norma Subjektif Terhadap Minat Berkunjung Wisatawan Pascapandemi Covid-19 (Survei Pada Pengunjung Saung Bali Karawang) - Shelly Wahyuni; Abdul Yusuf (Peneliti.net, 2022)
This study aims to examine and analyze the influence of attitude and subjective norms on tourists intention to visit post-pandemic Covid-19 (survey of visitors at Saung Bali Karawang). This study uses quantitive methods with descriptive and verification approaches. Popularity in this study is visitors at Saung Bali Karawang, using Slovin’s formula to determine the number of samples, the result obtained were 242 people/respondent. The sampling method used in this research is Non-probability Sampling with Purposive technique. This study uses bright scale analysis techniques and path analysis with SPSS 25 and Microsoft Excel 2010 data processing software. The result showed that the variables Attitude, Subjective Norms on Intention to Visit each get an average of 985.2, 935.4 and 954.6 meaning thal all of these variables are considered good. The correlation coefficient between Attitude and Subjective Norms is 0,724 which means it has a strong, unidirectional and significant correlation. The partial effect of Attitude on Intention to Visit has a greater value of 11,4% while the partial effect of Subjective Norms on Intention to Visit is 9,04%. The simultaneous influence of Attitude and Subjective Norms on Intention to Visit obtained a value of 76% and the remaining 24% was influenced by other variables that not researched.